Current situation and barriers to women's leadership in health care education in Saudi Arabia: A cross-sectional study - Ohoud S. Almalki; Ahmed Ibrahim Fathelrahman; Osamah M. Alfayez; Ghada A. Bawazeer (Elsevier, 2024)
Background: The aims of the current study were to explore the true representation of female academic staff who have advanced to leadership positions in Saudi health academic institutions and to determine the possible barriers to women's advancement to leadership positions in academia. Methodology: This was a cross-sectional study conducted between August 2022 and August 2023 using an adapted self-reported online questionnaire via Google form. Data was analyzed descriptively and comparatively by presenting frequencies with percentages besides means with standard deviations across various background categories and comparing them using student t test. Results: A total of 115 educators in health care professions participated in the study, three fifths of them were Saudi and female, with the majority being married and employed by government organizations. The most impactful structural challenges for female leadership included the centralization of decision-making within the institution, unclear organizational bylaws for leadership qualifications and appointment processes, and the existence of a wide range of administrative units. The prevailing belief that men possess superior capacity and management skills compared to women in leadership roles and the reluctance to accept women's authority by their subordinates were identified as the most influential culture challenges for female leadership. Most influential personality-related challenges included difficulty of balancing professional responsibilities with family obligations, stress and tension arising from reconciling the needs of subordinates with organizational goals and the complexity of traveling for work. Conclusions: The study identified the most influential structural, culture, and personality-related barriers and other potential perceived challenges faced by female leadership. A collective effort involving academic institutions, leadership, and relevant stakeholders is critical to address these barriers. Academic institutions must eliminate these challenges to utilize female leaders' talent fully, as they contribute unique perspectives and skills to their institutions.